Integrasi Pengetahuan Interdipliner Pada Pembelajaran IPA Terpadu: Studi Kasus Pembelajaran IPA Di MTS Muhammadiyah Wuring - Ernaningsih, Dian; Wahyuningsih, Wahyuningsih; Febrianti, Nurrohmah A.; Amir, Muhammad A.; Mardia, Ainun (Educatio, 2025)
The integration of interdisciplinary knowledge in science learning provides students with opportunities to understand the connections between various scientific concepts and other disciplines. This study aims to describe teachers’ understanding of interdisciplinary knowledge integration in science learning and their ability to implement this approach at MTs Muhammadiyah Wuring. This study adopts a qualitative approach using a case study design, with data gathered through interviews, observations, and documentation. The results show that science teachers have made efforts to incorporate multiple disciplines into their lessons, such as connecting the biology topic of the nervous system with physics and chemistry, as well as relating electrical concepts to religious studies. However, challenges such as limited teacher knowledge in other disciplines, insufficient planning time, and a lack of professional training hinder effective interdisciplinary learning implementation. To address these challenges, collaboration among teachers from different academic backgrounds and the application of problem-based learning (PBL) have proven effective in enhancing students’ comprehension and critical thinking skills. Therefore, providing professional training and designing a more flexible curriculum are essential to optimizing interdisciplinary-based integrated science learning.